Language and Science: The Importance of English Language Learning for Students of the Physics Education Study Program - Zaitun Qamariah; Hadma Yuliani (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
English language learning is fundamental in students' physics education since it provides access to worldwide scientific literature, facilitates international collaboration, and allows for effective communication among scientists. This literature study emphasizes integrating English learning within the physics curriculum. By building bridges between language and science, students of physics education study programs can improve communication skills and share knowledge effectively at the international level. Through innovative approaches to learning, students can enhance their language skills and develop an in-depth understanding of physics concepts, preparing them for success in the academic and professional world.